MODEL PEMBELAJARAN PADA MASA PANDEMI COVID-19 DI SDK WEWO, KECAMATAN SATARMESE, KABUPATEN MANGGARAI - MIkael Nardi; Ermilinda Paramita Lantur; Rudolof Ngalu (Jurnal Literasi Pendidikan Dasar (JLPD), 2021)
This research was motivated by the problems in the field of education as a result of the Covid-19 pandemic, that learning could no longer be done face-to-face in the classroom. Thus, educational interaction certainly does not occur optimally. The purpose of this study was to describe the learning model during the Covid 19 pandemic at Wewo Elementary School, its implementation, and the challenges. This research is a qualitative research with descriptive type. Data collection techniques in the form of observation, interviews and documentation. The data analysis technique followed the interactive model of Milles and Hubberman, which consisted of the process of collection, reduction, presentation, conclusion and verification of data. The results showed that: (1) the learning model used by the teachers at Wewo Elementary School was the offline learning model. The use of this model was chosen because of the lack of infrastructure to carry out online learning. In addition, many students could not use cell phones for learning because their parents cound not afford it. Another reason was that the readiness of teachers to carry out offline learning is also minimal. (2) The process of implementing offline learning is carried out by giving assignments and hard copies. The teacher provides the hard copies and assignments to do at home, accompanied by parents. Students were required to take and collect the materials and assignments at school according to a predetermined schedule by following the health protocol. (3) The difficulty while applying the offline learning model was that the learning process couldnot run optimally. In fact, learning occurs in educational interactions between teachers and students, between students and friends, and students and various learning resources in and outside the school environment. However, as long as students study at home, the interactive process did not occur. Students only worked on assignments given by the teacher in the form of the photocopies. The number of materials and assignments without communication with the teacher makes students feel bored and bored. This has an impact on decreasing student learning outcomes.